EFFECT OF FINANCIAL RATIO ANALYSIS ON PROFIT GROWTH IN THE FUTURE(IN MINING COMPANIES REGISTERED ON THE INDONESIA STOCK EXCHANGE FOR THE 2013-2015 PERIOD) - Rhevinalda Bima Prakarsa (Jurnal Apresiasi Ekonomi, 2019)
Profit is the most desirable company information in financial markets,one way to predict the company's earnings are using financial ratios.In this research used five financial ratios to predict profit growth in the mining company listed on the Indonesia Stock Exchange (BEI).The sampling technique used purposive sampling, this research uses 15 sample companies. The purpose of this research is to determine the effect of financial ratio analysis (Quick Ratio, Debt to Equity Ratio, Debt to Equity Ratio, Total Asset Turnover, Inventory Turnover) partially and simultaneously influence on earnings growth.Results from this study showed that partially QR has a significant influence on earnings growth,DR does not have a significant effect on earnings growth, DER has a significant influence on earnings growth,TATO not have a significant effect on earnings growth, ITO has a significant effect on earnings growth. Simultaneously Quick Ratio, Debt to Total Assets Ratio, Debt to Equity Ratio, Total Asset Turnover, Inventory Turnover effect on profit growth. Keyword: Quick Ratio, Debt to Equity Ratio, Debt to Equity Ratio, Total Asset Turnover, Inventory Turnover, Profit Growth.